OP0309 Intestinal sclerostin/serotonin axis is modulated by dysbiosis and regulates ilc3 expansion in as patients. (15th June 2017) - Ciccia, F; Guggino, G; Rizzo, A; Milling, S; Luchetti, M; Baeten, D; Alessandro, R; Triolo, G
Abstract : Background: Sclerostin is an osteocyte-specific factor that binds to low-density lipoprotein receptor-related protein 5 (LRP5) inhibiting the Wnt signaling pathway and possibly contributing to the pathogenesis of Ankylosing spondylitis (AS). Subclinical gut inflammation observed in AS patients is characterized by the presence of dysbiosis and innate immune alterations. In the gut, LRP5 activation by unknown ligands inhibits serotonin production. Serotonin, by inducing glial derived neurotrophic factor (GDNF), controls ILC3 expansion, in the context of glial–ILC3–epithelial cell unit (GIECU). Sclerostin/serotonin axis has been never studied in AS. Objectives: Aim of this study was to evaluate whether sclerostin is produced in the gut; to study the sclerostin/serotonin axis in AS and the effect of sclerostin on enterochromaffin cells (EC); to evaluate the presence of intestinal GIECU in AS and the role of serotonin in modulating the production of GDNF on isolated intestinal glial derived cells. We finally studied the effect of GDNF on ILC3. Methods: Ileal, synovial and bone marrow (BM) expression of sclerostin, serotonin and GDNF were investigated by rt-PCR, immunohistochemistry and WB in 30 AS patients and 20 controls. Platelet and plasma unconjugated concentrations of serotonin were assessed by high-performance liquid chromatography (HPLC). Isolated bacteria from AS ileal biopsies were cultured with EC and serotonin expression evaluated by RT-PCR. Sclerostin and serotonin gut expression were evaluated in HLA-B27 TG rats before and after antibiotics treatment. EC were stimulated with sclerostin and the expression of THP1 assessed by RT-PCR. The presence of GIECU was studied by confocal microscopy analysis of GFAP/Tbet/Thy1. Isolated intestinal glial cells were stimulated with serotonin and the modulation of GDNF assessed by RT-PCR. The effect of GDNF on ILC3 was evaluated by flow cytometry. Results: Sclerostin was produced in the gut and down-regulated in AS. Up-regulation of serotonin was observed in the gut, in the synovia and plasma, but not in BM of AS. Isolated intestinal bacteria from AS reduced EC serotonin production. Sclerostin down-regulation and serotonin over-expression were observed in the gut of HLA-B27 TG rats where Antibiotics increased intestinal sclerostin production and reduced serotonin expression. Treatment of isolated gut EC with sclerostin down-regulated the expression of THP1. GDNF was over-expressed in AS gut and confocal microscopy analysis demonstrated the existence of glial-ILC3-epithelial cells unit in AS patients. Finally, serotonin induces the release of GDNF by isolated intestinal glial cells and recombinant GDNF expanded RET + ILC3. Conclusions: here we demonstrate for the first time that intestinal sclerostin is the ligand of LRP5 and modulates the release of serotonin. Sclerostin/serotin axis is dysregulated in AS patients and HLA-B27 TG rats. In HLA-B27 TG rats, antibiotics restored sclerostin production and serotonin expression indicating a role of dysbiosis in modulating sclerostin/serotonin axis. Serotonin seems to be an important regulator of ILC3 expansion by inducing the production of GDNF by enteric glial cells, in the context of glial-ILC3-epithelial cells unit. Disclosure of Interest: None declared